1994
DOI: 10.1007/bf00971585
|View full text |Cite
|
Sign up to set email alerts
|

Functional relationship between ammonia and gangliosides in brain

Abstract: The functional significance of ammonia production in brain under physiological or pathological conditions is not clearly known. NH4+ stimulates Na+, K+ activated ATPase causing stabilization of neuronal membranes of which gangliosides are major structural components. Moreover ammonia is known to inhibit lysosomal enzymes which include enzymes degrading gangliosides. Gangliosides have been shown to stimulate neuritogenesis in neuronal cultures and prevent the damage of the neurons from glutamate toxicity partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Indeed, although scantly investigated, some investigators reported increased ganglioside levels in ALS including GM2 ganglioside 142 , 173 , 174 . In line with ammonia’s role in ganglioside metabolism, Perez et al showed that ammonia causes leakage of Hexosaminidase A (Hex A), indicating GM2 accumulation 175 , 176 . Thus, ammonia-induced GM2 accumulation could partly explains the heightened vulnerability of motor neurons in ALS ( Figure 2 ).…”
Section: Impaired Lysosomal Ganglioside Clearancementioning
confidence: 95%
“…Indeed, although scantly investigated, some investigators reported increased ganglioside levels in ALS including GM2 ganglioside 142 , 173 , 174 . In line with ammonia’s role in ganglioside metabolism, Perez et al showed that ammonia causes leakage of Hexosaminidase A (Hex A), indicating GM2 accumulation 175 , 176 . Thus, ammonia-induced GM2 accumulation could partly explains the heightened vulnerability of motor neurons in ALS ( Figure 2 ).…”
Section: Impaired Lysosomal Ganglioside Clearancementioning
confidence: 95%
“…Indeed, although scantly investigated, some investigators reported increased ganglioside levels in ALS including GM2 ganglioside [136,166,167]. In line with ammonia's role in ganglioside metabolism, Perez et al showed that ammonia causes leakage of Hexosaminidase A (Hex A), indicating GM2 accumulation [168,169]. Thus, ammonia-induced GM2 accumulation could partly explains the heightened vulnerability of motor neurons in ALS (fig 2).…”
Section: Impaired Lysosomal Ganglioside Clearancementioning
confidence: 99%